Cytological patterns of bronchoalveolar lavage fluid in mechanically ventilated COVID‐19 patients on extracorporeal membrane oxygenation. (11th March 2022) - Voicu, Sebastian; Malissin, Isabelle; Pepin‐Lehaleur, Adrien; Sutterlin, Laetitia; Naim, Giulia; M'Rad, Aymen; Guerin, Emmanuelle; Ekherian, Jean‐Michel; Deye, Nicolas; Adle‐Biassette, Homa; Mégarbane, Bruno
Abstract: Introduction: Coronavirus disease‐2019 (COVID‐19) may lead to acute respiratory distress syndrome requiring extracorporeal membrane oxygenation (ECMO). Patterns of inflammatory bronchoalveolar cells in COVID‐19 patients treated with ECMO are not well described. Objective: We aimed to describe inflammatory cell subpopulations in blood and bronchoalveolar lavages (BALs) obtained in critically ill COVID‐19 patients shortly after ECMO implementation. Methods: BAL was performed in the middle lobe in 12 consecutive ECMO‐treated COVID‐19 patients. Trained cytologists analyzed peripheral blood and BAL cells using flow cytometry and routine staining, respectively. Data were interpreted in relation to dexamethasone administration and weaning from ECMO and ventilator. Results: High neutrophil proportions (66% to 88% of total cells) were observed in the absence of bacterial superinfection and more frequently in dexamethasone‐free patients (83% [82–85] vs. 29% [8–68], P = 0.006), suggesting that viral infection could be responsible of predominantly neutrophilic lung inflammation. Successful weaning from ECMO/ventilator could not be predicted by the peripheral white blood and BAL cell pattern. Conclusion: High neutrophil proportions can be observed in critically ill COVID‐19 patients despite the lack of microbiological evidence on BAL of bacterial superinfection. Dexamethasone was associated with lower neutrophil proportions in BAL. Our study was probably underpowered to provide BAL cell pattern helpful to predict weaning from ECMO/ventilator. Abstract : In critically ill COVID‐19 patients treated with ECMO, a high neutrophil proportion in bronchoalveolar lavage fluid is possible despite the absence of evidence for bacterial infection. Neutrophil proportion is significantly lower in patients treated with dexamethasone at the time of bronchoalveolar lavage.